Assessment Of Indoor Air Quality in Maritime Museum Malacca - Roy Hazeera,; Kamarul Aini Binti Mohd Sari,; Hilmi Bin Kosnin, (Progress in Engineering Application and Technology, 2023)
The Indoor Air Quality (IAQ) problems are not new in Malaysia, and an imbalance of IAQ in museums might pose risks to both people and collection objects by causing indoor gaseous pollution within the museum structure. Therefore, the objectives of this study are to identify the IAQ problems and measure the IAQ parameters in the Maritime Museum Melaka. The average results of the measurement sampling for 3 were compared to the indoor air quality levels in compliance with ASHRAE 55, ASHRAE 62.1, and ICOP standards. The methodology used for this research employ real-time monitoring using a 4-in-1 meter kit, IAQ meter, and anemometer. The data taken are compared. The average temperature in the Maritime Museum Melaka was measured to be 22.98°C, while the relative humidity was recorded at 59.19%. The air velocity inside the museum was found to be 0.35 m/s. Carbon monoxide levels were measured at 0.89 ppm, and carbon dioxide levels were observed at 850.50 ppm. The significance of this study is to provide benefits to the occupants, including visitors and employees, enabling frequent visits for knowledge acquisition and improved work productivity without affecting their health during their time inside the building. Furthermore, the study will benefit visitors, the government, and the private sector in sustaining their buildings. This research has successfully achieved its objectives by identifying IAQ problems, measuring relevant parameters, and proposing recommendations for improvement. The outcomes of this study have the potential to positively impact the indoor environment and the well-being of occupants in the Maritime Museum, setting a precedent for sustainable and healthy indoor spaces in heritage buildings.